Նորկտակարանական առակների ժանրը և դրանց մեկնության հիմնական մեթոդները - Բեյլերյան, Հովհաննես
Until the 19th century, there were no special studies of the New Testament parables of Jesus in the Armenian theological tradition. This was in keeping with a broader trend within patristic exegetics. However, in various genres of religious literature – such as commentaries on the entire text of the Bible, sermons, works of systematic theology and theological literature – we can find valuable evidence of the interpretation of parables by early Armenian authors, Step‘anos Siwnets‘i, Yovhannēs Tsortsorets‘i, Grigor Tat‘ewats‘i and others. Their approaches tended to focus on extracting edifying teachings as well as establishing correspondences between the parables and other biblical texts. So, early Armenian patristics provides a valuable source for reconstructing the first approaches to parables within this theological tradition. From the beginning of the 19th century, the parables of the New Testament began to be considered separately, and Bishop Petros Berdumyan published his Open Source, a complete study on the parables of the New Testament. The genre of New Testament parables can be described as a type of narrative literature that uses vivid and relatable stories to convey spiritual and moral lessons. Interpreting New Testament parables involves various methods, and different scholars and theologians may approach them differently. До XIX века в армянской богословской традиции, также как и в патристической экзегетике в целом, не было специальных исследований, посвященных новозаветным притчам. Однако в комментариях на другие библейские книги, в проповедях, в догматических сочинениях и прочей теологической литературе можно найти ценные свидетельства интерпретации притч ранними армянскими авторами – такими, как Степанос Сюнеци, Ованнес Тцортцореци, Григор Татеваци и другие. Они, как правило, стремились извлечь из притчи некое назидание, а также установить связь между притчами и другими библейскими текстами. Ранняя армянская патристика – ценный источник для реконструкции подобного подхода к притчам. С начала XIX века притчи Нового Завета стали рассматриваться сами по себе, было опубликовано исследование епископа Петроса Бердумяна, озаглавленное «Открытый источник», целиком посвященное притчам Нового Завета.
Keywords: Բանասիրություն